2009
DOI: 10.2527/jas.2008-1399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein supplementation on expression and distribution of urea transporter-B in lambs fed low-quality forage1

Abstract: Two experiments were conducted to determine the effects of ruminal protein degradability, supplementation frequency, and increasing dietary protein on the expression and distribution of urea transporter-B (UT-B) in lambs fed low-quality forage (mature crested wheatgrass hay; 4.2 to 4.7% CP). In Exp. 1, 15 Dorset wether lambs (initial BW=45.8+/-1.3 kg) were blocked by initial BW and assigned to 1 of 3 treatments within a randomized complete block design for 28 d, with supplements fed to achieve 7, 10, or 13% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
2
27
2
Order By: Relevance
“…Previous studies have shown that UT-B protein is present all along the gastrointestinal tract of both cows (Dix et al 2013) and sheep (Ludden et al 2009), in contrast to observations in rats (Collins et al 2011). In agreement with predictions based on the known regulators of urea transport, the observed ruminant UT-B abundance pattern appeared to be rumen [ small intestine & colon (Dix et al 2013).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Previous studies have shown that UT-B protein is present all along the gastrointestinal tract of both cows (Dix et al 2013) and sheep (Ludden et al 2009), in contrast to observations in rats (Collins et al 2011). In agreement with predictions based on the known regulators of urea transport, the observed ruminant UT-B abundance pattern appeared to be rumen [ small intestine & colon (Dix et al 2013).…”
Section: Introductionsupporting
confidence: 81%
“…UT-B transporter proteins have previously been reported in the parotid salivary gland of both sheep and cows (Ludden et al 2009;Dix et al 2013). Furthermore, two distinct UT-B urea transporter isoforms, UT-B1 and UT-B2, are known to be expressed in the rumen of these species (Stewart et al 2005;Lu et al 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Instead, an increase in UT-B expression has been found in the rumen epithelium of concentrate-fed steers, which was associated with higher concentrations of SCFA and a lower pH in the rumen (49). The same trend has also been observed in lambs and heifers that received a diet rich in easily fermentable substrata (35,40), and in calves received low-protein solid feed (7). These findings suggest that microbial metabolites play a role in regulating UT-B.…”
supporting
confidence: 59%
“…The future will show whether long-term effects of butyrate on urea transport are indeed related to a higher density of urea transporters in the ruminal tissue or whether concomitant increases in ruminal surface area are sufficient to explain these effects (24,90). In general, however, the demonstration of an effect of dietary changes on the expression of gastrointestinal urea transporters in ruminants has been challenging (18,48,51,61,80).…”
mentioning
confidence: 99%